Circ_SPG11 plays contributing effects on IL-1β-induced chondrocyte apoptosis and ECM degradation via miR-665 inhibition-mediated GREM1 upregulation - Ouyang, Xiao (Clinical immunology (Orlando, Fla.), 2021)
Copyright © 2021 Elsevier Inc. All rights reserved.